2014
DOI: 10.3389/fnins.2014.00041
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin enhances attention to the eye region in rhesus monkeys

Abstract: Human and non-human primates rely on the ability to perceive and interpret facial expressions to guide effective social interactions. The neuropeptide oxytocin (OT) has been shown to have a critical role in the perception of social cues, and in humans to increase the number of saccades to the eye region. To develop a useful primate model for the effects of OT on information processing, we investigated the influence of OT on gaze behavior during face processing in rhesus macaques. Forty-five minutes after a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
63
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 56 publications
13
63
0
Order By: Relevance
“…Given the similarities between monkeys and humans in the neural circuitry underlying social cognition (19), the rhesus macaque could be an ideal animal model to examine the effects of OT. To date, only a few studies have investigated the behavioral consequences of OT administration in monkeys (20)(21)(22)(23)(24)(25). Consistent with the human literature, these studies have found that intranasal administration of OT affects social behavior and cognition in monkeys, Significance Oxytocin (OT), a mammalian hormone, may serve as a treatment for psychiatric disorders because of its beneficial effect on social behavior.…”
mentioning
confidence: 82%
See 3 more Smart Citations
“…Given the similarities between monkeys and humans in the neural circuitry underlying social cognition (19), the rhesus macaque could be an ideal animal model to examine the effects of OT. To date, only a few studies have investigated the behavioral consequences of OT administration in monkeys (20)(21)(22)(23)(24)(25). Consistent with the human literature, these studies have found that intranasal administration of OT affects social behavior and cognition in monkeys, Significance Oxytocin (OT), a mammalian hormone, may serve as a treatment for psychiatric disorders because of its beneficial effect on social behavior.…”
mentioning
confidence: 82%
“…Scanning began about 40 min after each treatment. A 40-min delay between drug administration and the start of scanning is similar to the timing used in previous monkey and human studies (20)(21)(22)53), as elevations of OT concentration in cerebrospinal fluid have been found ∼40 min after OT administration in monkeys (20,35,36) and humans [AVP, similar to OT with only a two-amino acid difference (54)]. The three monkeys were scanned in two separate sessions per treatment (placebo or OT), resulting in a total of 30 runs (60 condition repetitions) per monkey per treatment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In visual exploration studies, subjects are generally not rewarded for fixating on particular visual scene elements, to avoid biasing the gaze patterns toward these rewarded locations. A part of the visual exploration literature focuses on gaze patterns during free-viewing of ethologically or socially relevant stimuli, such as faces or body parts of conspecifics or other species (Dal Monte et al, 2014;Ghazanfar et al, 2006;Gothard et al, 2004;Tomonaga, 2009, 2010;Sigala et al, 2011). In this context, gaze patterns are thought to be driven by the need to make predictions about the intentions of other agents (Cannon et al, 2012;Kano and Call, 2014;Southgate et al, 2007), which might be relevant for guiding future behaviors.…”
Section: Introductionmentioning
confidence: 99%